Pentecostal Pedagogy: Spirit-Led Teaching Practice - O'Keefe, Dean D. (Pneuma, 2026)
In 2001, Jeffrey Hittenberger proposed a Pentecostal philosophy for education. With the growth of global Pentecostalism, many Pentecostal educational institutions have come into existence. Initially, colleges began as non-accredited practical ministry training Bible schools but have become well-established accredited liberal arts colleges and universities. Pentecostal colleges not only seek to apply their Pentecostal distinctive but must also comply with government standards. Within the context of Pentecostal higher education, the question on how to apply a Pentecostal worldview in the classroom remains of utmost importance. This article builds on the work started by Hittenberger, exploring how teachers integrate a Pentecostal worldview in the classroom, based on interview data from thirty-seven Australian tertiary teachers who identified personally with a Pentecostal worldview. The article discusses three key elements of a Pentecostal pedagogy.